THE ROLE OF SPIRITUAL CARE TOWARD MOTIVATION OF HEALING TO ELDERLY PATIENTS - Wahyuningsih, Aries; Kinasih, Karina Dinda (Jurnal Penelitian STIKES Kediri, 2012)
Elderly age is a person or population aged 60 years and over. Elderly undergo a process of decline of the body functions either biological, psychological and social functions, so that that condition may cause various problems, one of those problem is decreasing function of the body. During suffering illness, elderly patients in hospiritualtal need to get the attention not only on the biological aspect, but also the other aspects. The interventions that can be given to elderly patients in hospiritualtals to achieve the optimal quality of life by giving motivation of healing through spiritual care by the spiritualritual officers. The objective of this research was to analyze the correlation between the role of spiritual care and motivation of healing to elderly patients at Ward Kediri Baptist Hospiritualtal. The design used in this research was cross sectional. The populations were all employees of the spiritual department in hospiritualtal and elderly patients at ward kediri baptist hospiritualtal. The samples were 80 respondents using purposive sampling technique. The independent variable in this research was the role of spiritual care, and the dependent variable was the motivation of healing. The data was collected using observation and questionnaire to elderly patients as respondents, then analyzed using Spearman's Rho test with significance level Î± â‰¤ 0,05. The result of this research showed that statistical test of Spearman's Rho got value Ï = 0.000 which means that ho was rejected and ha was accepted with correlation coefficient 0.574. The conclusion of the research, there was the correlation between the role of spiritual care and motivation of healing to elderly patients at Ward Kediri Baptist Hospiritualtal.